2009
DOI: 10.1017/s0022109009090188
|View full text |Cite
|
Sign up to set email alerts
|

Hedge Funds for Retail Investors? An Examination of Hedged Mutual Funds

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 85 publications
4
62
0
1
Order By: Relevance
“…Agarwal, Boyson, and Naik (2009) study the performance of "hedged mutual funds," whereas Cici, Gibson, and Moussawi (2010) and Nohel, Wang, and Zheng (2010) investigate the potential conflicts of interest arising from the side-by-side management. Nohel et al (2010) find no conflicts of interest because mutual funds managed by side-by-side managers consistently outperform peer mutual funds after the manager enters the side-by-side arrangement.…”
mentioning
confidence: 99%
“…Agarwal, Boyson, and Naik (2009) study the performance of "hedged mutual funds," whereas Cici, Gibson, and Moussawi (2010) and Nohel, Wang, and Zheng (2010) investigate the potential conflicts of interest arising from the side-by-side management. Nohel et al (2010) find no conflicts of interest because mutual funds managed by side-by-side managers consistently outperform peer mutual funds after the manager enters the side-by-side arrangement.…”
mentioning
confidence: 99%
“…Mutual funds, accessible to a larger array of investors, attempt to mimic hedge funds without utilizing leverage or short-selling (predicting that the price of a security would go down) the market. Still, these hedged mutual funds do not offer the same performance or niche as regular hedge funds [7]. Additionally, the inability of mutual funds to short the stock market results in a significant fall in value during times of recession [8].…”
Section: Financial Alternativesmentioning
confidence: 99%
“…Therefore, many seek financial assistance from funds that actively manage their clients' money. For example, current middle-class individuals could allocate their capital to mutual funds (which are managed by a group of financial experts), which pool investor money (with variable minimum investment requirements usually between $1,000 and $5,000) and invest in stocks and bonds without the use of leverage or short selling [7]. In contrast to hedge funds, mutual funds are strictly regulated by the Securities and Exchange Commission to follow these rules, in order to mitigate risk for investors.…”
Section: Level I Need Assessmentmentioning
confidence: 99%
“…These mutual funds are referred to as HMFs or absolute return mutual funds. Unlike the hedge fund industry, HMFs are regulated by the Securities and Exchange Commission (Agarwal et al, 2009).…”
Section: Hmf Datamentioning
confidence: 99%
“…In the only other study on HMFs that we are aware of, Agarwal et al (2009) showed that the superior performance of HMFs over traditional mutual funds (TMFs) was driven by managers with hedge fund experience, and that HMFs have significantly higher turnover and Although the Eta model concerns itself with economic risk and not risk associated with returns, we will nevertheless examine returns of MERP via traditional measures. Further inspection of MERP and HMFs are therefore conducted on their conditional volatilities and their conditional correlations with the SPX, which are estimated, respectively, by the GARCH and DCC models.…”
Section: Minimum Economic Risk Investmentmentioning
confidence: 99%